Creating Infrastructures for Latino Mental Health - Buki, Lydia P.; Piedra, Lissette M. (Springer New York : Imprint: Springer, 2011)
The growing Latino population of the United States stands poised to shape the nation's future throughout the twenty-first century, yet serious obstacles hinder the full participation of the Latino community in American society.  Access to mental health care poses a particular challenge for many segments of the population.  Although significant scholarship has focused on the delivery of culturally competent practice, few academic resources address systemic issues that affect the actual delivery of services to Latino clients.  In response, Creating Infrastructures for Latino Mental Health provides the first interdisciplinary guide aimed at improving access to mental health services.  Experts from several specialties provide state-of-the-art analyses and innovative strategies for tackling the structural, organizational, and linguistic issues that contribute to service inequities.  Collectively, the book chapters call attention to clinical, geographical, and social contexts, as well as to populations as varied as breast cancer survivors, rural "new growth communities," and unaccompanied immigrant youth.  The authors provide an exquisite array of intersecting topics linked by a common theme: the need for a broad social response to transform mental health service for Latinos.  Among the topics covered:  ·         Infrastructure development aimed at specific dimensions of structural inequality ·         The role of government in facilitating the development of infrastructures ·         The need for federal policy to protect immigrants and aid in their incorporation   ·         Building local infrastructures attuned to the specific needs of communities ·         Developing a bilingual workforce through interdisciplinary collaboration, organizational planning, and training of staff and interpreters ·         Addressing the mental health needs of Latino youth in the juvenile justice system ·         Expanding educational opportunities for first-generation college students ·         Supporting Latino families caring for persons with serious mental illness "An extraordinary contribution to multiple stakeholders....Provides guideposts for policy-makers, administrators, researchers and clinicians alike." -- Patricia Arredondo, EdD, Associate Vice Chancellor for Academic Affairs, University of WI-Milwaukee  "This book's comprehensive compendium of knowledge of Latino mental health makes it indispensable reading not only for mental health professionals, social workers and educators but for all those interested in the psychology and culture of the fastest growing population in America." -- Pastora San Juan Cafferty, PhD, Professor Emerita, School of Social Service Administration, University of Chicago  "This book addresses tremendous gaps in the fields of Latino mental health and healthcare. Packed with useful information, innovative perspectives, and actionable policy recommendations, this interdisciplinary effort undoubtedly will become a "go-to" resource in meeting the mental-health needs of Latinos." -- Glenn Flores, MD, FAAP, Director, Division of General Pediatrics, Professor of Pediatrics, Clinical Sciences, and Public Health, The Judith and Charles Ginsburg Chair in Pediatrics, UT Southwestern Medical Center and Children's Medical Center Dallas.